BRAZILIAN MINING: ECONOMIC SIGNIFICANCE, MARKET FAILURE, AND THE STRATEGIC IMPERATIVE OF INTERNALIZING SOCIO-ENVIRONMENTAL COSTS - Edstron Secundino Santos, Júlio (Revista Gênero e Interdisciplinaridade, 2026)
This research addresses the intricate relationship between Brazilian mining and its complex socio-environmental externalities, examining how the activity, vital for national development and global trade, consistently fails to internalize its social costs. Employing bibliographic review and the hypothetico-deductive method, the study applies the Coase Theorem to diagnose the allocative inefficiency within the sector, grounded in the premise that the persistence of impacts stems from the failure of the theory’s ideal assumptions. The research’s significance lies in its capacity to map market imperfections and power asymmetries, utilizing concrete cases and Supreme Federal Court (STF) rulings (CFEM, TFRM) to illustrate the failure of private negotiation. The findings demonstrate that, due to exorbitantly high transaction costs and the ambiguity of rights over public goods, the Coasian ideal proves impracticable. The definitive solution resides in coercive state intervention (the “Corrective State”) and the adoption of “quasi-Coase” mechanisms, such as the ESG Agenda and the Social License to Operate (LSO), as the sole viable pathways to enforce cost internalization and ensure that mining development is, in effect, socially and environmentally sustainable.